Diarrhoeal diseases and its relation to WaSH practices and MPN count among under-five children residing in Resettlement colony, Delhi - Sangma, Risa Vernette Nengminza; Rasania, Sanjeev Kumar; Prasuna, Joysula Gnani; Das, Ranjan; Jais, Manoj (Indian Journal of Community Health, 2020)
Background: Globally, diarrhoeal diseases are the second leading cause of death among under 5 children and India alone accounts for 100,000 lives annually, third highest in the world. In low and middle-income countries, contaminated water has been the major source of diarrhoeal diseases and lack of improper WaSH (Water, Sanitation and Hygiene) practices accounts for 90% of the total death. Aims and Objective: To find out the burden of diarrhoea and its relation to WASH practices among children and mothers/care givers and Presumptive Coliform count of drinking water. Materials and Methods: A community-based cross-sectional study conducted in Resettlement colony, Delhi. A total of 553 under 5 children were studied after attaining consent from mothers/care givers. MPN count per 100 ml was measured from drinking water storage vessel. Result: Prevalence of diarrhoea was found to be 40.70%, being higher among children aged between 13-24 months (57.3%). Out of the total water samples, 37% of samples were unsatisfactory, 36% suspicious and 22% satisfactory. None of the samples were found to be satisfactory. Lack of WaSH practices was observed among mother/care givers. Conclusion: Understanding the factors influencing the occurrence of diarrhoeal diseases and drinking water quality will help reduce the burden of diarrhoeal diseases.